THE IMPACT OF OIL PRICE FLUCTUATIONS ON IRAQ'S FOREIGN EXCHANGE RESERVES FROM 2005 TO 2022 - Zeina Tariq Ali Neama (Scholars Digest Publishing, 2024)
The study aims to determine the impact of global oil price fluctuations on Iraq's foreign exchange reserves, as the importance of foreign exchange reserves has increased in recent years due to Iraq's economic and political situation. Therefore, maintaining an adequate share of reserves has become one of the most essential tools for achieving financial stability. Consequently, it is necessary to study and analyze the factors that affect the proportion of foreign exchange reserves held by the central bank. Since the Iraqi economy is rentier, these reserves are primarily affected by oil price fluctuations. Standard models are used to study the extent to which foreign exchange reserves are affected by oil price fluctuations. The study came to several conclusions, the most important of which is the existence of a direct relationship between oil prices and foreign exchange reserves. Importance of research The importance of this study is that foreign exchange reserves are significant at both the local and international levels, and it is necessary to analyze the factors that affect foreign exchange reserves, the most important of which may be oil price fluctuations. Search problem Due to the increase in oil exports, foreign cash flows have increased, contributing to the central bank's foreign exchange reserves. Therefore, the research question can be asked: Do oil price fluctuations negatively or positively impact foreign exchange reserves? Research hypothesis The research hypothesis assumes that global oil price fluctuations positively affect Iraq’s foreign exchange reserves. Research Objective The study aims to show the impact of oil price fluctuations on Iraq's foreign exchange reserves from 2005 to 2022. Spatial and temporal boundaries Iraqi studies were selected as an example of research and period (2005-2022).
Keywords: (oil price fluctuations, foreign reserves, ARDL).